The Role of Love Languages in Enhancing Marital Communication - Rostami, Mehdi; Saadati, Nadereh; Parsakia, Kamdin; Gharibian, Fatemeh (KMAN Counseling & Psychology Nexus, 2025)
This study aims to explore the role of love languages in enhancing marital communication among couples in Tehran. This qualitative study employed semi-structured interviews with 24 participants (12 married couples) selected through purposive sampling. Data were collected until theoretical saturation was reached and analyzed using thematic analysis with NVivo software. The study identified four main themes: understanding love languages, expression of love, communication challenges, and strategies for improvement. Understanding and practicing love languages fostered emotional intimacy and relational satisfaction. Participants emphasized cultural influences, mutual adaptation, and the importance of consistent communication. However, challenges such as misinterpretation and emotional barriers highlighted the need for awareness and tailored interventions. Love languages significantly enhance marital communication and satisfaction, but their effectiveness depends on cultural context, individual differences, and mutual effort. Incorporating love languages into therapeutic practices can provide meaningful tools for couples to navigate relational challenges and strengthen their bonds.